2017
DOI: 10.18203/2349-2902.isj20171514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of suspicious Hirschsprung disease in children using radiologic investigation method: a prospective observational study

Abstract: Background: Hirschsprung disease (HD) is a developmental disorder characterized by absence of ganglia in the distal colon, resulting in a functional obstruction. It is a common cause of pediatric intestinal obstruction. Objective of present study was to evaluate a checklist of radiologic and clinical signs to determine the probability of HD in suspicious patients.Methods: In a diagnostic accuracy study, 19 children with clinical manifestations of HD attended pediatric OPD in a tertiary care teaching hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…We found the sensitivity of the delayed film to be 81.25% which is similar to data from prior studies that have shown sensitivities between 60% to 99% [9][10][11][12]. With respect to specificity and PPV, in comparison to previous studies, we obtained a high value of 90.9% and 97.5%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found the sensitivity of the delayed film to be 81.25% which is similar to data from prior studies that have shown sensitivities between 60% to 99% [9][10][11][12]. With respect to specificity and PPV, in comparison to previous studies, we obtained a high value of 90.9% and 97.5%.…”
Section: Discussionsupporting
confidence: 88%
“…With respect to specificity and PPV, in comparison to previous studies, we obtained a high value of 90.9% and 97.5%. In a previous study, specificity and PPV were reported as 7.6% and 20.6%, respectively, while another study described the specificity and PPV to be 73.7% and 83.9% [9,12].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The presence of megarectum, common in patients with severe intestinal constipation, the occurrence of air leak during the insufflation of the balloon, and the incorrect positioning of the catheter in the sphincter complex are potential causes for misdiagnosis (2,4). In addition, this method is less available than BE, because of the equipment costs and to the need for an experienced examiner, mainly to evaluate infants younger than 1 year (2,9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the applicability and diagnostic capacity of the RSI in the diagnostic investigation for HD (7)(8)(9)(10). They have shown important differences and conflicting results (7)(8)(9)(10).…”
mentioning
confidence: 99%